An Exploratory Study of the Reading Habits of Urban Malaysians and its Impact on Academic Achievement - Ponnudurai, Prema; Kimberly Irawan, Michelle (International Journal of Engineering and Technology, 2018)
Recently, greater awareness has been reported regarding the problems associated with the weak reading habits of Malaysian millennials and its lack. In a world where harnessing and using knowledge is of utmost importance, firstly, understanding the reading habits is vital before moving forward to address this issue and emphasising its development. Therefore, the objective of this study was to investigate the reading habits of university students and to identify its correlation to their academic performance. A small random sample of fifty undergraduate students from an urban private university in Selangor participated in this quantitative study. Statistical analysis (SPSS) was used to analyse the academic and recreational reading habits and ascertain the correlation between reading and academic performance. The findings revealed the types of readings preferred by undergraduate students, the frequencies and found insignificant correlation between reading habits and academic performance due to the low reading practise. This is concluded by suggestions for academics, students and curriculum designers in tackling this long standing issue in Malaysia.Â Â